Material Planning Analysis with Material Requirement Planning Method in High-rise Building Projects - Awati, Mawinda Oktrify; Putra, I Nyoman Dita Pahang (Indonesian Journal Publisher, 2024)
Planning material supplies well is very important in implementing construction projects to ensure smoothness and efficiency. Smoothness includes thorough planning, including ensuring materials are met as planned, while efficiency aims to reduce time and cost. In this study, material planning will be carried out using the Material Requirement planning (MRP) method, using three different lot measurement techniques, namely Lot for Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). The MRP method is carried out to accurately calculate the amount of material needed to avoid excessive material inventory levels. After the MRP method, the most optimal number of orders and the total cost required for each lot measurement technique are obtained. The results of this study show that the LFL technique produces the optimum number of orders for gelam wood, plywood, reinforcement, bendrat wire, and ready mix concrete. Meanwhile, for materials such as lubricating oil, meranti wood, randu wood, and nails, it is optimal to order using the POQ technique.